NEUROSIENCE DAN PENGALAMAN KEAGAMAAN ( SPRITUAL) KASUS KORUPSI - Hammi Latifah (IAIN Padangsidimpuan, 2017)
Day by day people are always faced with deviant behavioral symptoms. Lying is no longer in a personal capacity even though it includes self-denial, but is done through its power, the power of the public. A power which, according to a healthy soul and a clear mind, is to carry out the mandate of the people. What is the relitasnya? That is a lie to lie covering these (political) power processes is a